Factors influencing residents’ inclination towards engaging in the recycling of electric vehicle batteries - Chao Zuo; Xuqiang Yan; Ziyi Chen; Wenbo Wei; Meina Gao; Yuting Ling; Fenping Zhu; Bei Liu; Hongwei Zhou; Dong Xu; Mengjun Zhang (Humanities & Social Sciences Communications)
Abstract In Hangzhou, the rapid development of electric vehicles has led to the first large-scale battery retirement trend in recent years. Despite ongoing efforts by the government and enterprises to promote the formal recycling of used batteries, recycling rates remain low. Therefore, exploring the factors that influence consumers’ willingness to recycle retired batteries is key to improving the recovery rate of residents. In this study, from July 1 to July 31, 2023, we conducted an offline survey in Hangzhou with multi-stage stratified sampling. A total of 657 questionnaires were collected and analyzed as the basic data for our research. The results indicated that personal norms, subjective norms, and recycling intentions were all significantly positively correlated. Ascription of responsibility was associated with stronger personal norms, while policy incentives were associated with stronger subjective norms. However, the impact of product after-sales on intention to recycle was not significant, and residents have low recycling cognition of recycling behavior. These results suggested that the norm activation model was applicable for examining consumer recycling behavior in the context of electric vehicle batteries. The study contributed to the theoretical understanding of pro-environmental behavior and provides practical insights for policymakers and enterprises aiming to enhance consumer participation in battery recycling initiatives.